La auditoría operativa como herramienta y su relación con el área de tesorería en la Municipalidad Provincial de Maynas 2021 - Chapoñan Arancibia, Ana Tereza (2023)
The present research work entitled “The Operational Audit as a Tool and its Relationship with the Treasury Area in the Provincial Municipality of Maynas 2021 is descriptive, correlational level and non-experimental design that included a sample of 25 workers from the institution. mayor of Maynas, it was proposed to determine the relationship between the operational audit and the treasury area in the period 2021. The investigation concludes that the Operational Audit is directly related to the Treasury Area in the period 2021, demonstrated with the Correlation Coefficient r = 0.419; and the Bilateral Significance = 0.010 obtained in Table No. 09. Likewise, it has been proven that specific hypothesis 1 in the operational audit according to the instrument is notably associated with the collection of RDR entries in the Provincial Municipality of Maynas 2021, having obtained a Correlation Coefficient r = 0.512 and the Bilateral Significance = 0.002 obtained in Table No. 10. On the other hand, in specific assumption 2 in the operational audit according to the instrument, it is notably associated with the making of disbursements in the Municipality Provincial de Maynas 2021, having obtained a Correlation Coefficient r = 0.804; and the Bilateral Significance = 0.040 obtained in Table No. 11. Finally, the operational audit according to the instrument is notably associated with the control and monitoring in the Provincial Municipality of Maynas 2021, having obtained a Correlation Coefficient r = 0.179; and the Bilateral Significance = 0.012 obtained in Table No. 12.